Monetary and Fiscal Policies in the Transition to EMU: an Overview of the Spanish Experience - Bajo-Rubio, Oscar; Díaz-Roldán, Carmen (Publishing House of the Wrocław University of Economics, 2009)
One of the main achievements of the EU is the Economic and Monetary Union (EMU). This consists of the adoption of a single currency, the euro, which also implies a common monetary policy for all participating countries. Spain is one of the participating members of EMU since its start. Before the formation of EMU, and particularly after joining the EMS, Spanish monetary policy had followed a Taylor-type rule with a high coefficient on the inflation target. This behavior led to a significant fall in the inflation rate, which allowed Spain to be able to join EMU from its start. In contrast, after joining EMU and increase in both inflation rates and the differential with the euro zone can be observed. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 22-29